5x-(2)=2x+13

Simple and best practice solution for 5x-(2)=2x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-(2)=2x+13 equation:


Simplifying
5x + -1(2) = 2x + 13

Multiply -1 * 2
5x + -2 = 2x + 13

Reorder the terms:
-2 + 5x = 2x + 13

Reorder the terms:
-2 + 5x = 13 + 2x

Solving
-2 + 5x = 13 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-2 + 5x + -2x = 13 + 2x + -2x

Combine like terms: 5x + -2x = 3x
-2 + 3x = 13 + 2x + -2x

Combine like terms: 2x + -2x = 0
-2 + 3x = 13 + 0
-2 + 3x = 13

Add '2' to each side of the equation.
-2 + 2 + 3x = 13 + 2

Combine like terms: -2 + 2 = 0
0 + 3x = 13 + 2
3x = 13 + 2

Combine like terms: 13 + 2 = 15
3x = 15

Divide each side by '3'.
x = 5

Simplifying
x = 5

See similar equations:

| 1.0t+6.34t-2.12t= | | 4x-13=33 | | -21=k+9 | | c=(-20)+(-8) | | y=x^3+18x^2+77x+60 | | 2x^2+2x+14=0 | | 6.3+4=5.3x | | 5x+11=3x-8 | | Log[4](28)-log[4](28)= | | 2x^2-x-66=0 | | 7-5-3=46 | | 5x-3(2x-1)=25-3x | | x-(x*.05)=450 | | 25x-4=-45x+12 | | 10+(-14)= | | -86=-7x+4(3x-9) | | 10x-18=32+5x | | 4x-2(6x+8)=40 | | 2/3(x-3)=4x+18 | | 6[x-(2-x)]=-4(8x+3) | | 6-10x=27-3x | | 25x-45x=-4+12 | | 535=55x | | -2x+10=-18-6x | | -5+2u=-7 | | 3n+75=50+2n | | -(-7+4x)=8x+18 | | 19=3+4v | | 6-6x=-12-4x | | 180=(3x+y-10)+x+5 | | 180=3x+y-10+x+5 | | N-25=5 |

Equations solver categories